THE EFFECT OF RESPONSIVENESS AND RELIABILITY ON CUSTOMER SATISFACTION AT WARUNG RAWIT TAMAN PALEM - Grace Syela; Dewanta Facrureza (ZILLZELL MEDIA PRIMA, 2024)
The significant increase from year to year makes that culinary today is not only to meet food needs but also has become a lifestyle among the community. This will increase the intensity of competition in the culinary business itself starting from the products offered to services to customers such as responsiveness and reliability. This study aims to examine the relationship between responsiveness and reliability to customer satisfaction at Warung Rawit Taman Palem. This study used quantitative type research methods with an associative approach using questionnaires to 100 respondents. This study uses a test method consisting of validity test, reliability test, classical assumption test, multiple linear regression analysis, partial T test, simultaneous F test and coefficient of determination. The results of this study explain that Responsiveness and Reliability have a simultaneous and partial effect on Customer Satisfaction at Warung Rawit Taman Palem.